A study on anti-stress property of Nardostachys jatamamsi on stress induced Drosophila melanogaster - Shilpashree R.; Sathish Kumar B.Y. (Journal of Stress Physiology & Biochemistry, 2011)
Stress is a feeling that’s created when we react to particular events. It s the body’s way of rising to a challenge and preparing to meet a tough situation with focus, strength, stamina, and heightened alertness. As a result of the stress immune system can be suppressed by chronic stress opening to increased infections and increasing the risk of autoimmune diseases. So one has to learn away to overcome stress. Here is an attempt made to overcome the stress induced in Drosophila melanogaster a model organism, in this study. Methotrexate is used to induce the stress at different concentration taking different group of flies and a Nardostachys jatamamsi plant extract having antistress property is used to relieve the stress induced. This stress relieve measured by the various stress related enzymes like catalase and Superoxide dismutase by this antistress property of the plant Nardostachys jatamamsi was shown.